Competition between exchanges: Euronext versus Xetra - Maria Kasch-Haroutounian; Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2006)
Exchanges in Europe are in a process of consolidation. After the failure of the proposed merger between Deutsche Börse and Euronext, these two groups are likely to become the nuclei for further mergers and co-operation with currently independent exchanges. A decision for one of the groups entails a decision for the respective trading platform. Against that background we evaluate the attractiveness of the two dominant continental European trading systems. Though both are anonymous electronic limit order books, there are important differences in the trading protocols. We use a matched-sample approach to compare execution costs in Euronext Paris and Xetra. We find that both quoted and effective spreads are lower in Xetra. When decomposing the spread we find no systematic differences in the adverse selection component. Realized spreads, on the other hand, are significantly higher in Euronext. Neither differences in the number of liquidity provision agreements nor differences in the minimum tick size or in the degree of domestic competition for order flow explain the different spread levels. We thus conclude that Xetra is the more efficient trading system.
Keywords: G10; G15; 330; Competition between exchanges; bid-ask spread